Response of the Quasi‐Biennial Oscillation to a warming climate in global climate models - Richter, Jadwiga H.; Butchart, Neal; Kawatani, Yoshio; Bushell, Andrew C.; Holt, Laura; Serva, Federico; Anstey, James; Simpson, Isla R.; Osprey, Scott; Hamilton, Kevin; Braesicke, Peter; Cagnazzo, Chiara; et al. (Quarterly journal of the Royal Meteorological Society, 2022)
We compare the response of the Quasi‐Biennial Oscillation (QBO) to a warming climate in eleven atmosphere general circulation models that performed time‐slice simulations for present‐day, doubled, and quadrupled CO2 climates. No consistency was found among the models for the QBO period response, with the period decreasing by 8 months in some models and lengthening by up to 13 months in others in the doubled CO2 simulations. In the quadrupled CO2 simulations, a reduction in QBO period of 14 months was found in some models, whereas in several others the tropical oscillation no longer resembled the present‐day QBO, although it could still be identified in the deseasonalized zonal mean zonal wind timeseries. In contrast, all the models projected a decrease in the QBO amplitude in a warmer climate with the largest relative decrease near 60 hPa. In simulations with doubled and quadrupled CO2, the multi‐model mean QBO amplitudes decreased by 36 and 51%, respectively. Across the models the differences in the QBO period response were most strongly related to how the gravity wave momentum flux entering the stratosphere and tropical vertical residual velocity responded to the increases in CO2 amounts. Likewise it was found that the robust decrease in QBO amplitudes was correlated across the models to changes in vertical residual velocity, parametrized gravity wave momentum fluxes, and to some degree the resolved upward wave flux. We argue that uncertainty in the representation of the parameterized gravity waves is the most likely cause of the spread among the eleven models in the QBO's response to climate change. The response of the Quasi‐Biennial Oscillation (QBO) to a warming climate was examined in eleven general circulation models. No consistency was found among the models for the QBO period response. In contrast, all the models projected a decrease in the QBO amplitude in a warmer climate.